RITZ ANALYSIS OF THE FOURIER SPECTRUM OF CH3OH BETWEEN 350 AND 950 CM(-1) - Ioli, N.; Moruzzi, G.; Riminucci, P.; Strumia, F.; Moraes, João Carlos Silos [UNESP]; Winnewisser, B. P.; Winnewisser, M. (Academic Press Inc. Jnl-comp Subscriptions, 1995)
A new ''Ritz'' program has been used for revising and expanding the assignment of the Fourier transform infrared and far-infrared spectrum of CH3OH. This program evaluates the energy levels involved in the assigned transitions by the Rydberg-Ritz combination principle and can tackle such perturbations as Fermi-type resonances or Coriolis interactions. Up to now this program has evaluated the energies of 2768 levels belonging to A-type symmetry and 4133 levels belonging to E-type symmetry of CH3OH. Here we present the assignment of almost 9600 lines between 350 and 950 cm(-1). The Taylor expansion coefficients for evaluating the energies of the levels involved in the transitions are also given. All of the lines presented in this paper correspond to transitions involving torsionally excited levels within the ground vibrational state. (C) 1995 Academic Press, Inc.